2015
DOI: 10.1038/srep14090
|View full text |Cite
|
Sign up to set email alerts
|

Role of Src in Vascular Hyperpermeability Induced by Advanced Glycation End Products

Abstract: The disruption of microvascular barrier in response to advanced glycation end products (AGEs) stimulation contributes to vasculopathy associated with diabetes mellitus. Here, to study the role of Src and its association with moesin, VE-cadherin and focal adhesion kinase (FAK) in AGE-induced vascular hyperpermeability, we verified that AGE induced phosphorylation of Src, causing increased permeability in HUVECs. Cells over-expressed Src displayed a higher permeability after AGE treatment, accompanied with more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 50 publications
7
48
0
Order By: Relevance
“…We have revealed a significant exudation of FITC-dextran from mesenteric venules in AGE-treated wild type mice. However, this exudation was markedly reduced in RAGE knockout mice, which further confirmed the role of RAGE in vascular hyperpermeability in vivo [35]. Moreover, we have shown that LPS caused significant rearrangement of cytoskeletal filament F-actin in insolated wild-type mouse pulmonary microvascular endothelial cells (PMVECs).…”
Section: Discussionsupporting
confidence: 63%
“…We have revealed a significant exudation of FITC-dextran from mesenteric venules in AGE-treated wild type mice. However, this exudation was markedly reduced in RAGE knockout mice, which further confirmed the role of RAGE in vascular hyperpermeability in vivo [35]. Moreover, we have shown that LPS caused significant rearrangement of cytoskeletal filament F-actin in insolated wild-type mouse pulmonary microvascular endothelial cells (PMVECs).…”
Section: Discussionsupporting
confidence: 63%
“…Previously, we have shown that Src acts like a signal node and elicits an endothelial permeability increase upon AGE stimulation, whereas both the inhibition of AGEs binding to RAGE and the downregulation of Src significantly ameliorated AGE‐induced F‐actin rearrangement and hyperpermeability. Consistently, Src upregulation with the dominant active mutant, Src K298M, duplicated the barrier disruptive effect . The main underlying mechanism involved has been investigated in our laboratory.…”
Section: Mechanism Of Age‐induced Endothelial Dysfunctionmentioning
confidence: 68%
“…First of all, smoking has chronic effects, by diminishing nitric oxide availability and endothelial celldependent vasodilation, which lead to an enhanced oxidative stress, glomerulosclerosis and tubular atrophy [53,54]. Moreover, cigarette smoke contains glycotoxins which induce advance glycation end products (AGEPs) and thus directly promote pathological vascular changes [55]. On the other hand, evidence of a link between smoking habit and Doppler-RI impairment are limited.…”
Section: Plos Onementioning
confidence: 99%